Genetic Variants of Milk Protein Genes and Their Association with Milk Components in Holstein Friesian Cattle - Santiananda Arta Asmarasari; Cece Sumantri; A Gunawan; E Taufik; Anneke Anggraeni (Jurnal Ilmu Ternak dan Veteriner, 2020)
Protein content in milk is an important indicator of milk. Accordingly, genetic improvement to produce Holstein Friesian (HF) dairy cattle is important. The objective of this study was to evaluate the genetic variant of milk protein genes and its effect on milk component traits of Holstein Friesian (HF). A total of 100 HF were used in this study. The HF cattle used have physiological status in the lactation period 1 up to 3 and lactation change of 1 up to 12 months. Genotype variants of milk protein genes were identified using Real Time-Polymerase Chain Reaction method.  Analysis of milk component was carried out covering the component of protein, fat, lactose, and solid non-fat (SNF) by using a milk quality measuring device (Lactoscan). Genotyping of cattle blood samples consisted of DNA extraction, genes amplification using the RT-PCR method. The result showed that protein milk was significantly affected (p<0.05) by the genetic variants of CSN1S1-192 and CSN2-67 genes. Fat milk was significantly affected (p<0.05) by the genetic variants of CSN1S1-192 and CSN3 genes.  Meanwhile, solid non-fat milk was significantly affected (p<0.05) by the genetic variants of CSN-BMC9215, CSN-BMC6334, CSN1S1-14618, CSN2_67, and CSN3 genes. Lactose milk was significantly affected (p<0.05) by the genetic variants of CSN-BMC9215 and CSN2-67 genes. It was concluded that genetic variants of the milk protein genes have an association with the component of cow's milk (protein, fat, solid non-fat, and lactose).